Efficacy and pharmacogenomic biomarkers in breast cancer. (April 2012) - Paul, Asit K; Schwab, Richard B
In patients with breast cancer, a number of biomarkers, such as estrogen receptor, progesterone receptor and HER2, are part of routine work-up and used to guide endocrine, cytotoxic and HER2-targeted treatment. Interaction among these markers may also impact on treatment response and is being investigated. Multigene assays have reached varying levels of validation and clinical use as predictive biomarkers of cytotoxic therapy in specific clinical situations. A number of pharmacogenomic biomarkers based on germline polymorphisms have reached some degree of validation for predicting variation in treatment response and treatment-associated adverse effects. The challenge of validating biomarkers will be exacerbated as the cost of nucleic acid sequencing rapidly declines and more potential biomarkers emerge. New, carefully designed approaches will be needed to address this issue and realize the potential of biomarkers in breast cancer.